Salience and situatedness in the language of the blind - Stanojević, Mateusz-Milan; Geld, Renata (2006)
This paper is based on the assumption that human knowledge is perceptual in character, and that this is reflected in the use of construal operations in language (Langacker 1987 ; Fauconnier 1994 ; Talmy 2000 ; Tomasello 1992 ; Croft and Cruse 2004). In line with this, our aim is to demonstrate to what extent the conceptual content in the language of the blind is different from the conceptual content in the language produced by the sighted. More specifically, the paper explores the vividness of mental imagery in 15 blind persons which is contrasted to a group of 19 sighted persons. In the first group, six persons were congenitally blind (three were totally blind, two with the reduction of vision to 5% of normal, and one person was sensitive to light), two were legally blind with the reduction of vision to 10% of normal, four persons were totally blind as a result of sudden loss of vision, and three persons were born as partially-sighted and totally lost their vision in their early twenties. The instrument used to induce mental imagery was based on tasks designed for the Vividness of Visual Imagery Questionnaire (David Marks, City University, London). Both groups were asked to imagine three scenes that allow for different sensory modalities to be activated. All of the responses were written, and the time limit was ten minutes per task. The analysis that followed was qualitative. The basic assumption was that the language of the blind will reflect rich mental imagery based on different sensory inputs, making the most effective use of touch compensating for their lack of vision. The central finding of the study is that the blind persons’ construal involves two specific differences from the contrast group. Firstly, there is a shift in scalar adjustment from schematicity to specificity, and secondly the vantage point tends to indicate a different position of the speaker. For example, in their mental image of a scene with a forest, a lake and a mountain, most sighted subjects include all three elements in more or less the same arrangement, usually ignoring the details. In contrast, the blind give detailed descriptions of different aspects of the three mentioned elements (the leaves on the trees, the texture of the trunk, the temperature of the water, etc.). Thus, because of their perceptual modalities, the prevalent aspects of construal in the blind are different than in the sighted. However, this in no way means that the language of the blind is to be taken as deficient, but rather gives further support to the cognitive linguistic claim concerning the subjective character of language. Croft, W. and A. Cruse. 2004. Cognitive Linguistics. Cambridge University Press Fauconnier, G. 1994. Mental Spaces. Cambridge University Press Langacker, R. 1987. Foundations of Cognitive Grammar. Vol. 1. Stanford University Press Talmy, L. 2000. Toward a Cognitive Semantics. Vol 1. The MIT Press Tomasello, M. 1992. First verbs: a case study of early grammatical development. Cambridge University Press
Projekt MZOS
Projekt MZOS
ENG